The human–primate interface in the New Normal: Challenges and opportunities for primatologists in the COVID‐19 era and beyond. Issue 8 (20th July 2020) - Lappan, Susan; Malaivijitnond, Suchinda; Radhakrishna, Sindhu; Riley, Erin P.; Ruppert, Nadine
Abstract: The emergence of SARS‐CoV‐2 in late 2019 and human responses to the resulting COVID‐19 pandemic in early 2020 have rapidly changed many aspects of human behavior, including our interactions with wildlife. In this commentary, we identify challenges and opportunities at human–primate interfaces in light of COVID‐19, focusing on examples from Asia, and make recommendations for researchers working with wild primates to reduce zoonosis risk and leverage research opportunities. First, we briefly review the evidence for zoonotic origins of SARS‐CoV‐2 and discuss risks of zoonosis at the human–primate interface. We then identify challenges that the pandemic has caused for primates, including reduced nutrition, increased intraspecific competition, and increased poaching risk, as well as challenges facing primatologists, including lost research opportunities. Subsequently, we highlight opportunities arising from pandemic‐related lockdowns and public health messaging, including opportunities to reduce the intensity of problematic human–primate interfaces, opportunities to reduce the risk of zoonosis between humans and primates, opportunities to reduce legal and illegal trade in primates, new opportunities for research on human–primate interfaces, and opportunities for community education. Finally, we recommend specific actions that primatologists should take to reduce contact and aggression between humans and primates, to reduce demand for primates as pets, to reduce risks of zoonosis in the context of field research, and to improve understanding of human–primate interfaces. Reducing the risk of zoonosis and promoting the well‐being of humans and primates at our interfaces will require substantial changes from "business as usual." We encourage primatologists to help lead the way. Abstract : Example of human–primate interface: Highly provisioned Southern pig‐tailed macaques ( Macaca nemestrina ) at Lumut Mangrove Park, Malaysia receiving daily food handouts from park visitors shortly before the COVID‐19 lockdown in March 2020 (photo by Susana Almagro). HIGHLIGHTS: In this commentary, we briefly introduce the problem of zoonosis between humans and nonhuman primates; discuss challenges that the COVID‐19 pandemic has created for primates and for primate researchers; identify opportunities created or revealed by the COVID‐19 pandemic to reduce the intensity of problematic human–primate interfaces, reduce the risk of zoonosis, and reduce trade in primates; identify opportunities for research on human–primate interfaces in light of the COVID‐19 pandemic; and make specific recommendations for researchers in light of the pandemic and beyond‐pandemic realities.